Initial and long-term antithrombotic therapy after left atrial appendage closure with the WATCHMAN. Issue 7 (28th May 2020) - Ledwoch, Jakob; Sievert, Kolja; Boersma, Lucas V A; Bergmann, Martin W; Ince, Hüseyin; Kische, Stephan; Pokushalov, Evgeny; Schmitz, Thomas; Schmidt, Boris; Gori, Tommaso; Meincke, Felix; Protopopov, Alexey Vladimir; et al.
Abstract: Aims: Evidence regarding post-procedural antithrombotic regimen other than used in randomized trials assessing percutaneous left atrial appendage (LAA) closure is limited. The present work aimed to compare different antithrombotic strategies applied in the real-world EWOLUTION study. Methods and results: A total of 998 patients with successful WATCHMAN implantation were available for the present analysis. The composite ischaemic endpoint of stroke, transitory ischaemic attack, systemic embolism and device thrombus, and the bleeding endpoint defined as at least major bleeding were assessed during an initial period (from implant until first medication change) and long-term period (from first change up to 2 years). The antithrombotic medication chosen in the initial phase was dual antiplatelet therapy (DAPT) in 60%, oral anticoagulation (OAC) in 27%, single antiplatelet therapy (SAPT) in 7%, and no medication in 6%. In the second long-term phase, SAPT was used in 65%, DAPT in 23%, no therapy in 8%, and OAC in 4%. No significant differences were found between the groups regarding the ischaemic endpoint both in the initial period (Kaplan–Meier estimated rate 2.9% for DAPT vs. 4.3% for OAC vs. 3.9% for SAPT or no therapy) and in the second period (4.2% for SAPT vs. 1.8% for DAPT vs. 3.5% for no therapy). With respect to bleeding events, the only difference was found in the initial phase with a higher incidence in patients under SAPT or no therapy. Conclusions: Tailored antithrombotic treatment using even very reduced strategies such as SAPT or no therapy showed no significant differences regarding ischaemic complications after LAA closure.